Social Media Influencers and the Shaping of Cultural Awareness among Algerian Youth (El-Wahat Journal for Research and Studies, 2026)
This research underscores the significance of a profound understanding of the role of social media influencers and investigates how their impact on the cultural awareness of youth in Algeria, as well as the shaping of their cultural values and attitudes, can be enhanced. This is achieved through observations and a review of multiple prior studies. The findings indicated that these influencers possess the capability to disseminate knowledge and interact with young audiences in ways that foster dialogue and critical thinking. The study concludes by presenting a set of recommendations that emphasize the necessity of guiding the role of social media influencers towards positively enhancing cultural awareness and directing them to provide more valuable content. Furthermore, it highlights the importance of channeling efforts to encourage youth to develop critical thinking skills to understand the true impact of the information they receive via social media.
Keywords: Algerian Youth, Critical Thinking, Cultural Awareness, Cultural Values, Social Media Influencers